DIE ÜBERTRAGUNGSPROBLEMATIK ALS THERAPEUTISCHE GRUNDBEZIEHUNG. EINE RADIKAL PHÄNOMENOLOGISCHE AUSEINANDERSETZUNG MIT KONZEPTEN DER TIEFENPSYCHOLOGIE UND PSYCHOANALYSE JACQUES LACANS - KÜHN, Rolf (Studia Universitatis Babeș-Bolyai Philosophia, 2019)
Transference, as well as counter-transference are both central to the praxis of psychoanalytical therapy. They emerge from the encounter with the patient who is caught in libidinal conflicts (Freud) and in the imaginary chain of signifiers (Lacan). Affective effects stemming from transference must, therefore, be taken into account in order to clarify their unconscious connection to the symbolic as well as to the real. Phenomenologically speaking, this corresponds to an original dimension of being-affected, a dimension prior to any sort of interpretation. It aims at liberating desire (désir) by making jouissance possible as an act that does not lead to a hypostasis of the law (Phallus).